The Mechanisms of Yu Ping Feng San in Tracking the Cisplatin-Resistance by Regulating ATP-Binding Cassette Transporter and Glutathione S-Transferase in Lung Cancer Cells - Du, Yingqing; Zheng, Yuzhong; Yu, Ciel Xiaomei; Zhong, Lishan; Li, Yafang; Wu, Baomeng; Hu, Weihui; Zhu, Elsa Wanyi; Xie, Venus Wei; Xu, Qitian; Zhan, Xingri; Huang, Yamiao; et al. (Frontiers in Pharmacology, 2021)
Cisplatin is one of the first line anti-cancer drugs prescribed for the treatment of solid tumors; however, the chemotherapeutic drug resistance is still a major obstacle of cisplatin in treating cancers. Yu Ping Feng San (YPFS), a well-known ancient Chinese herbal combination formula consisting of Astragali Radix, Atractylodis Macrocephalae Rhizoma and Saposhnikoviae Radix, is prescribed in a decoction to treat immune disorders in clinic. To understand the fast-onset action of YPFS as an anti-cancer drug resistance of cisplatin, we provided detail analysis of intracellular cisplatin accumulation, cell viability, expressions and activities of ATP-binding cassette transporters and glutathione S-transferases (GSTs) in YPFS-treated lung cancer cell lines. In cultured A549 or its cisplatin-resistance A549/DDP cells, application of YPFS increased accumulation of intracellular cisplatin, resulting in lower cell viability. In parallel, the activities and expressions of ATP-binding cassette transporters and GSTs were down-regulated in the presence of YPFS. The expression of p65 subunit of NF-κB complex was reduced by treating the cultures with YPFS, which led to a high ratio of Bax/Bcl-2, i.e. increasing the rate of cell death. Prim-O-glucosylcimifugin, one of the abundant ingredients in YPFS, modulated the activity of GSTs, and then elevated cisplatin accumulation, resulting in increased cell apoptosis. The present result supports the notion of YPFS in reversing drug resistance of cisplatin in lung cancer cells by elevating of intracellular cisplatin, and the underlying mechanism may be down regulating the activities and expressions of ATP-binding cassette transporters and GSTs.